2022
DOI: 10.1371/journal.pgph.0001235
|View full text |Cite
|
Sign up to set email alerts
|

“Testing for malaria does not cure any pain” A qualitative study exploring low use of malaria rapid diagnostic tests at drug shops in rural Uganda

Abstract: The World Health Organization recommends all suspected malaria cases be confirmed with a parasitological test, typically a rapid diagnostic test (RDT), prior to treatment. Despite recommendations, many fevers presenting at private drug shops are treated presumptively as malaria without diagnostic testing. The purpose of this qualitative study was to describe community perceptions of RDTs and explore ways to improve malaria case management at drug shops in Bugoye, western Uganda. A total of 63 in-depth intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Shopkeepers who recently adopted rapid diagnostic testing reported selling antimalarials less often than they previously had when treatment routes were based only on symptoms. This reaffirms prior studies detecting high rates of overdistributing antimalarials for non-malaria cases [7173]. The more prudent use of antimalarials after the introduction of rapid testing encourages upscaling access to diagnostic testing for malaria in order to prevent the overuse of antimalarials and accelerated resistance.…”
Section: Discussionsupporting
confidence: 80%
“…Shopkeepers who recently adopted rapid diagnostic testing reported selling antimalarials less often than they previously had when treatment routes were based only on symptoms. This reaffirms prior studies detecting high rates of overdistributing antimalarials for non-malaria cases [7173]. The more prudent use of antimalarials after the introduction of rapid testing encourages upscaling access to diagnostic testing for malaria in order to prevent the overuse of antimalarials and accelerated resistance.…”
Section: Discussionsupporting
confidence: 80%
“…When RDTs were conducted, clients who tested negative sometimes still purchased antimalarials (36%). Qualitative research in this setting found that these antimalarial purchases stemmed from vendor and client distrust in negative RDT results, and fear or uncertainty about treatment next steps for conditions other than malaria ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The content of sensitization should emphasize the benefits of testing at private retailers without diminishing other healthcare sectors: for example, a qualitative study suggested that sensitization efforts should focus on emphasising the need for testing regardless of the location (public or private), and leverage the trust in drug shops, which could increase uptake at private retailers without diminishing the work of public healthcare [ 59 ]. In the reviewed studies, over 80% of customers were satisfied with POCTs [ 34 , 72 74 ], citing the convenience of testing locations [ 51 , 74 ], as they would not have to travel to hospitals [ 40 ].…”
Section: Resultsmentioning
confidence: 99%